PENGARUH LIKUIDITAS, LEVERAGE, UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN TUNAI DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Dian Masita Dewi (Jurnal Bisnis dan Ekonomi, 2016)
The purpose of this research to clarify the effect of liquidity , leverage , size of the company to cash dividend policy with profitability as an intervening variable. The population in this study are all companies listed on the Indonesia Stock Exchange period 2012 - 2014 totaling 141 companies. The samples using purposive sampling method which was then acquired 19 manufacturing companies. The analytical method used is path analysis. The results obtained in this study is the liquidity does not affect the profitability and the size of the company while the leverage effect on profitability. Profitability affect the cash dividend policy. Profitability can not be intervening variables for liquidity, leverage and the size of the company against cash dividend policy. Conclusions from this research that the amount of leverage and the size of the company proved capable of affecting low profitability. Companies that have a large profitability does not always give a high dividend. Suggestions for investors who want high dividends should choose companies with low debt levels. For companies should fulfill their financial filled with their own capital. For further research should use a broader sample. keyword: liquidity , leverage, size of the company, cash dividend policy and  profitability